How physical exercise with others and prioritizing positivity contribute to (work) wellbeing: a cross-sectional and diary multilevel study - Gil-Beltrán, Ester; Coo, Cristian; Meneghel, Isabella; Llorens, Susana; Salanova, Marisa (Frontiers in Sports and Active Living, 2024)
This work is a dual study employing a cross-sectional approach and a diary method to investigate how physical exercise becomes a habit. Guided by the upward spiral theory of lifestyle change, we examined the role of prioritizing positivity and engaging in physical exercise with others as advantageous resources, and their impact on the relational loop of physical exercise behavior, emotions, and engagement. The first study involved a sample of 553 participants, and the second included 146 participants, all of whom were employed and regularly engaged in physical exercise. We utilized Structural Equation Modeling and multilevel analysis for the respective studies. The first study's results indicate that individuals exercise more when they experience higher levels of engagement and positive emotions, particularly when exercising with others and prioritizing positivity. The second study's findings reveal that prioritizing positivity acts as a precursor to positive emotions during physical exercise, which in turn reinforces the relational loop between emotions and exercise behavior. Both studies conclude that individuals who prioritize positivity experience better psychological well-being and higher engagement in physical exercise.